APLIKASI E -PAYROLL GURU MENGGUNAKAN RULE BASED SYSTEM PADA SEKOLAH MTs NURUL IMAN TANJUNG MORAWA - Mutiara Pasaribu; Antoni; Tasliyah Haramaini (Jurnal Riset Multidisiplin Edukasi, 2026)
Advances in information technology are encouraging educational institutions to optimize administrative management more effectively, including the teacher payroll process. At MTs Nurul Iman Tanjung Morawa, payroll processing is still done manually, resulting in late payments and potential errors in salary calculations. This research aimed to design and develop a rule-based e-payroll application for teachers as a solution to these problems. The system was developed using Agile methods, encompassing planning, design, coding, and testing. The system was built by implementing payroll rules that cover the calculation of teaching hours, allowances, and deductions based on teacher attendance. The results showed that the resulting e-payroll application is capable of automatically calculating salaries, providing payslips, and generating payroll reports quickly and accurately. Implementing this system makes the teacher payroll process more efficient and minimizes the risk of calculation errors that often occur in manual systems.